Paternalistic leadership and employee creativity: A mediated moderation model. (14th March 2017) - Wang, Yating; Tang, Chaoying; Naumann, Stefanie E; Wang, Yong
Abstract: Our study extends the relationship between paternalistic leadership and employee creativity by identifying employee organizational identification as a mediator and employee perceived job security as a moderator. Results based on the data of 378 employees from a large bank in China indicated that employee perceived job security moderated the relationship between the morality component of paternalistic leadership and employee creativity. In addition, employee organizational identification mediated the relationship between the morality component of paternalistic leadership and employee creativity. We discuss implications for research on paternalistic leadership and employee creativity.